Re-designing a Polestar 2 interior door panel: Aiming to reduce the environmental impact by half - Ahammer, Marina; Van Rosse, Monique (My University, 2022)
This bachelor’s thesis was written in cooperation with the car manufacturer Polestar in Gothenburg focusing on sustainability by using alternative materials and design strategies to reduce the carbon dioxide emissions by 50% during the manufacturing of a Polestar 2 interior door panel. The materials used to manufacture a car’s interior account for 10% of all the emissions generated during car production. The project has included an analysis of the current problems with the existing door panel regarding materials and emissions created but has also worked with examining a door panel's lifecycle from a cradle-to-grave perspective. This was explored by performing a Life Cycle Analysis with two different softwares, openLCA and GRANTA Edupack. The collected data and the impact assessment calculations created a baseline when scouting for new and more sustainable material options. Methods used for the Life Cycle Assessment have been retrieved from literary studies as well as from the company’s own LCA report 2021. Furthermore, more creative methods for conceptualisation, idea generating and material scouting have been used. To visualise how certain materials would be perceived by customers, concepts were visualised in Photoshop. These concepts were evaluated using decision making matrices which led to the final concept. The final concept was modelled in Catia V5 and rendered in Autodesk VRED. The result was a door panel made of cork and a coffee-polymer, which reduced the carbon footprint by 68%. The project shall provide a base for further research in material development within the automotive industry.
Keywords: materials, sustainability, LCA, Life Cycle Assessment, car interior, emissions